2021
DOI: 10.1111/tid.13697
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining mask momentum in transplant recipients

Abstract: The widespread use of facemasks has been a crucial element in the control of the SARS‐CoV‐2 pandemic.  With mounting evidence for mask efficacy against respiratory infectious diseases and greater acceptability of this intervention, it is proposed that masking should continue after the pandemic has abated to protect some of our most vulnerable patients, recipients of stem cell and solid organ transplants. This may involve not only masking these high‐risk patients, but possibly their close contacts and the healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Several sites have reported on successes in shifting transplant to home-based rather than hospital-based care [ 85 , 86 ]. Widespread routine masking has resulted in marked reduction in the spread of community respiratory virus infections in HSCT recipients, formerly a relatively frequent cause of morbidity and mortality in this population, with some calling to “maintain mask momentum” in this population in the post-pandemic era [ 87 , 88 ]. Undoubtedly there is much more we will learn from the pandemic, both with regard to how best to manage and mitigate COVID-19 in HSCT recipients, but also how best to approach post-transplant vaccinations and prevention of infection more broadly.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Several sites have reported on successes in shifting transplant to home-based rather than hospital-based care [ 85 , 86 ]. Widespread routine masking has resulted in marked reduction in the spread of community respiratory virus infections in HSCT recipients, formerly a relatively frequent cause of morbidity and mortality in this population, with some calling to “maintain mask momentum” in this population in the post-pandemic era [ 87 , 88 ]. Undoubtedly there is much more we will learn from the pandemic, both with regard to how best to manage and mitigate COVID-19 in HSCT recipients, but also how best to approach post-transplant vaccinations and prevention of infection more broadly.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…This could be explained by a T-cell response in the absence of humoral responses, and by more conscious use of non-pharmacological protective measures. Indeed, strong evidence has shown that routine masking protects against the spread of respiratory viruses, including SARS-CoV-2 [ 29 ]. However, more research is needed to determine the benefit of universal masking for SOT patients.…”
Section: Discussionmentioning
confidence: 99%